Work Motivation, Job Satisfaction and Employee Performance - Rezki Nurdiansyah; Siti Mariam; Muhammad Asrar Ameido; Abdul Haeba Ramli (Universitas Trisakti, 2020)
This investigation goals to anatomize the influence of work motivation on employee performance intercede by employee job satisfaction. The data is obtained directly through distributing questionnaires via google docs and whatsapp to employees who work at Bank Rakyat Indonesia. The number of respondents in this determination was 160 people. The results of hypothesis testing show : Work motivation has a positive and significant effect on employee performance, job satisfaction and employee performance through job satisfaction, then Job satisfaction has a positive effect and significant on employee performance.